Effectiveness Numbered Head Together Type Cooperative Learning Model to Improve Arabic Language Learning Outcomes - Sri Wahyuni; Munirul Abidin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Arabic language learning is a lesson that is difficult to understand and comprehend by most students one of them is students at SMP Muhammadiyah 2 Kalasan, because the learning model applied by the teacher is a lecture model that makes students quickly feel bored in participating in learning. Therefore, the type cooperative learning model is a solution that is in accordance with the situation of students in grade 7 SMP Muhammadiyah 2 Kalasan. This study aims to determine the effectiveness of the Numbered Head Together type cooperative learning model in improving learning outcomes in Arabic language subjects. The research method used is quantitative pseudo-experimental type true experimental with post test only control group design. Researchers will use taking 50 samples. This study uses two groups, namely the experimental group and the control group by giving treatment and post test in each class. The sampling used is probability sampling, researchers use data collection methods only from post test results. The results showed that the Numbered Head Together type cooperative learning model was effective in improving the Arabic language learning outcomes of 7th grade students of SMP Muhammadiyah 2 Kalasan compared to learning with the lecture method. Evidenced by the results of the independent sample T-test analysis, it is known that the 2 tailed sig value of 0.000 is smaller than 0.05, so Ho is rejected Ha is accepted. It is concluded that there is a significant difference in the average student learning outcomes between learning using the Numbered Head Together model and learning that does not use the Numbered Head Together model, namely the lecture method. For future research If you want to use the Numbered Head Together model in learning, adjust it first to the needs of students and do as much as possible so that the resulting output is optimal. In addition, teachers can develop more creative learning models so that students learn fun and understand easily.